DETERMINANTS OF SAVINGS CULTURE AMONG FARMERS’ COOPERATIVE SOCIETIES MEMBERS IN KABBA/BUNU LOCAL GOVERNMENT AREA, KOGI STATE, NIGERIA (FUDMA Journal of Agriculture and Agricultural Technology, 2023)
The importance of agricultural cooperative in enhancing productivity through adequate access to resources by farmers cannot be overemphasized. However, farmers are constraint in terms of financial participation towards boosting the level of productivity. Therefore, this study examined the determinants of saving culture among farmers’ cooperative societies members in Kabba/Bunu Local Government Area of Kogi State, Nigeria. Structured questionnaire was used to elicit primary data from 100 respondents proportionately selected from four cooperative societies using simple random sampling technique. Descriptive statistics and multiple regression analysis were used to analyze the data. The study revealed that 53.1% of the cooperative farmers were male while 46.9% were females, and the average age of the farmers is 34 years. About (43.9%) of the farmers belong to thrift and credit type of cooperative societies. Major determinants of saving culture were age, sex of farmer, level of income, household expenses, interest rate charged on loan, duration of loan repayment. The farmers faced the problem of low-income level, high cost of labour, inadequate infrastructure and natural disaster. It is therefore recommended that farmers in the study area should improve on their farming practices which can boost their farm income level, maintain moderate number of children and promptly repay loan borrowed. Education and training of cooperative leaders and members is paramount to the success and growth of the cooperatives. Therefore, stakeholders should assist in this direction.
Keywords: Determinants; savings; cooperatives; multiple regression; farmers